Energy Efficient Source Location Privacy Protecting Scheme in Wireless Sensor Networks Using Ant Colony Optimization - Liming Zhou; Qiaoyan Wen (International Journal of Distributed Sensor Networks)
Wireless sensor networks consist of various sensors with limited power, which collect different useful and privately relevant information. We pay attention to some issues related to sensor's location privacy. Ant colony optimization provides a natural and intrinsic way of exploration of search space for preserving sensor's location privacy. In this paper, we focus on protecting the sensor's location by introducing suitable modifications to sensor routing to make it difficult for an eavesdropper to find the original location. And we propose an energy efficient preserving sensor's location privacy based on ant colony optimization scheme, which is a flexible routing strategy to protect the sensor's location. Simulation results show that our strategy can efficiently reduce the chance of packets being detected and prolong the network lifetime. And the adversary can find it difficult to find the exact location of the source node.